Electrical Consequences of Protein-Glucose Interactions in the Human Kidneys - Nieto-Chaupis, Huber (2021)
As it is well-known, diabetic patients might to develop crisis in the renal apparatus either in the middle or long time [1]. This crisis is imminently attained to the high concentrations of glucose. In fact, under the theoretical assumption that the ions of glucose molecules push out giant molecules of albumin then one might to expect a direct dependence among them from classical electrodynamics basis. In this paper, this dependence and the physics-based relationships are derived. The theoretical result of this paper would be of interest in all those new applications of advanced sensors that might be able to measure status of both glucose and albuminuria. Thus, one can carry out a complete diagnostic of kidney status from glucose values. The paper presents theoretical predictions of glucose and albumin interactions while both of them are located along the renal glumerulus.